The Politics of Prevention: Polarization in How Workplace COVID-19 Safety Practices Shaped the Well-Being of Frontline Service Sector Workers. Issue 1 (February 2023) - Woods, Tyler; Schneider, Daniel; Harknett, Kristen
The COVID-19 pandemic dramatically reshaped the labor market, especially for service sector workers. Frontline service sector workers, already coping with precarious working conditions, faced proximate risks of COVID-19 transmission on the job and navigated new workplace safety measures, including masking, social distancing, and staying home while sick, all in a polarized political environment. We examine polarization in the effects of COVID-19 workplace safety measures on workers' feelings of safety and well-being. Specifically, we examine how support for former President Trump moderates the relationship between COVID-19 safety practices (masking, social distancing, staying home while sick) and workers' feelings of safety and well-being. To do so, we draw on novel data collected by The Shift Project from 2, 039 service sector workers at 89 large firms during the COVID-19 pandemic. We find that workplace safety measures are positively associated with workers' self-assessments of feeling safe and with mental health, but only for Biden voters.